Prevalência e fatores associados à perda de olfato e/ou paladar em pessoas idosas hospitalizadas com Covid-19 no estado da Paraíba - Fernandes, Letícia de Carvalho Palhano Travassos (2023)
The sense of smell and taste are of utmost importance for human interaction and adaptation to the external environment. During aging, changes occur characterized by the decrease in physiological reserves and the increase in pathologies, which can result in alterations and declines in these senses. In older individuals, these changes can limit their activities and relationships with others, affect their safety and quality of life, and may indicate the presence of a disease, such as COVID-19. Therefore, these aspects, along with bed immobility due to the need for hospitalization, make older adults more vulnerable to complications, making this process complex. The aim of this study was to analyze the prevalence and factors associated with symptoms of loss of smell and/or taste in hospitalized older adults with COVID-19 in the state of Paraíba, Brazil. This is a quantitative, observational, cross-sectional, and retrospective study, derived from a database of patients with Severe Acute Respiratory Syndrome (SARS) hospitalized in the Unified Health System of Paraíba, included in the State Health Department database between January and December 2020 and notified in individual registration forms. The study was approved by the research ethics committee (nº. 4,174,541). Data on loss of smell and taste and clinical factors were selected, which were divided into signs and symptoms and comorbidities. In addition, information on ICU admission, use of ventilatory support, and case evolution was also collected. Data were analyzed using the PSPP and R® software. Descriptive analysis of quantitative data was performed by calculating the mean and standard deviation. The association analysis of clinical factors with changes in smell and/or taste was performed using Fisher's exact test, with a confidence interval of 95% and calculation of the prevalence ratio as a measure of association. Variables with p-values <0.2 in Fisher's exact test were added to the binary logistic regression model. In hospitalized older adults with COVID-19, the prevalence of loss of smell was 8%, loss of taste was 6.4%, and loss of smell and/or taste was 9.2%. The logistic regression model analysis revealed that the clinically associated factors significantly associated with loss of smell were fever, cough, sore throat, respiratory discomfort, diarrhea, vomiting, abdominal pain, fatigue, asthma, and ICU admission, the latter being the only considered protective factor. Regarding loss of taste, the model demonstrated a greater chance of occurrence in the presence of fever, cough, sore throat, diarrhea, abdominal pain, and recovery. Meanwhile, the presence of neurological disease and the B.1.1.28 or B.1.1.33 (VOC) variant showed a lower chance of developing this symptom. The model's results showed that the chances of developing loss of smell and/or taste are higher in the presence of fever, cough, sore throat, diarrhea, vomiting, abdominal pain, fatigue, and diabetes, and lower when the patient needs ICU admission. The results of this study contribute to a better understanding of the magnitude of loss of smell and taste in hospitalized older adults with COVID-19 and may help improve the screening of these symptoms based on knowledge of associated factors and collaborate for more assertive decision-making and management in this population.